JUAL BELI FOLLOWERS DALAM PRESPEKTIF HUKUM PERDATA DAN HUKUM ISLAM - Nasution, Mas Gabena; Pulungan, Sahmiar (Universitas Muhammadiyah Ponorogo, 2024)
Sales and purchases of followers are increasing in the general public. In these transactions, the seller offers a service to add followers online by receiving payment from the buyer. The seller then adds followers to the buyer's Instagram account according to the agreed amount and price. However, the followers sold were not only active accounts, but also passive accounts and fake bot accounts. The aim of this research is to explain how followers are added and distributed on Instagram, as well as whether these activities are regulated and benefited by civil and law in Indonesia, especially among Muslims. This research uses normative methods. The author argues that, depending on the approach used from the perspective of civil law and Islamic law, transactions of sale of followers can be detrimental to consumers, prevent debtors from fulfilling their obligations, and lead to non-performance. As one of the parties fails to fulfil its obligations, it constitutes a breach of contract and is automatically a violation of the law. In Islamic law, the goods traded must exist, be usable, and be useful to mankind. It is not lawful to sell something that is not his, because it is illegal to sell it according to Islamic law. Followers can disappear in an instant, because Instagram doesn't want that.